East Africa: The next game-changer for the global gas markets? - Manfred Hafner; Simone Tagliapietra (Fondazione Eni Enrico Mattei (FEEM), 2013)
The geographical distribution of African natural gas resources is going through a period of profound change as new gas discoveries in East Africa emerge to reshape the continent's energy landscape. This region is rapidly establishing itself as a world-class natural gas province and two countries have already emerged as key-players of this new African natural gas renaissance: Mozambique and Tanzania. This paper provides a comprehensive analysis of the gas developments in the region, which could well become the next game-changer of the global gas market.
Keywords: Q4; Q48; 330; Natural Gas; East Africa; Energy Geopolitics; Hydrocarbons; Exploration and Production